Analisis Efisiensi Produksi Usahatani Padi Sawah (Oriza Sativa L) di Kelompok Tani Beranga Indah Desa Magepanda Kecamatan Magepanda Kabupaten Sikka - Maria Elisabeth Delang; Sarlina Noni; Gabriel Otan Apelabi; Taras Iawan Saputera Wanda (Agriculture - Jurnal Ilmu Pertanian, 2024)
Production efficiency in lowland rice farming can be improved through enhancements in farmers’ managerial capabilities. These capabilities originate from the farmers themselves and are influenced by socio-economic factors. This study aims to determine the level of production efficiency of lowland rice farming in the Beranga Indah Farmer Group, Magepanda Village. The research method used is a survey method with a quantitative approach. The sampling technique applied was a saturated sample, involving 19 respondents. Data analysis employed the Cobb-Douglas production function and efficiency testing. The results of the study indicate that the factor that significantly (statistically) affects lowland rice production in the Beranga Indah Farmer Group is labor, with a significance level of 0.009. Meanwhile, the factors that do not have a significant effect are land area (0.278), seeds (0.183), pesticides (0.371), and fertilizer (0.286). The use of inputs such as land area, labor, seeds, pesticides, and fertilizer has not yet been technically, allocatively, or economically efficient, as the efficiency values of land area, seeds, pesticides, and fertilizer are greater than one; therefore, they are considered inefficient.